Describing Postpartum Contraceptive Counseling and Patient Satisfaction at a Large Urban Academic Medical Center [26A]. (May 2017) - Jou, Jessica; Findley, Molly; McMahon, Lauren; Kapedani, Arisa; Levi, Erika; Benfield, Nerys
Abstract : INTRODUCTION: Postpartum contraception is a powerful tool for reducing unintended pregnancy and optimizing birth spacing. In 2014 we initiated a comprehensive postpartum contraception counseling and provision program at our institution and subsequently evaluated the prevalence of counseling, satisfaction with counseling, and uptake of postpartum contraception. METHODS: During their postpartum hospitalization, women completed a survey assessing perinatal contraceptive counseling timing, locations, content, and satisfaction, along with demographic and labor characteristics, and subsequent contraceptive plans and uptake. A chart review confirmed medical and demographic data. Descriptive statistics were obtained and logistic regression was used to evaluate associations. RESULTS: Our 156 participants were primarily young, primiparous, non-white and had public insurance. 93% of women reported receiving contraceptive counseling: 82% antenatally, 69% intrapartum, and 61% postpartum. There was no difference in counseling prevalence by age, race, parity, preferred language, mode of delivery, or insurance type. 97% of patients reported high satisfaction with their contraceptive counseling. Most patients (60%) felt that counseling in antenatal care was optimal; 6% preferred intrapartum counseling. At discharge, 93% reported a plan for contraception use. 58% were discharged with a prescription for contraception, had an implant or IUD placed, or injection administered prior to discharge. CONCLUSION: We demonstrate that near universal contraceptive counseling is achievable in a diverse and socioeconomically disadvantaged population. This leads to a high uptake of postpartum contraception with high rates of satisfaction. Women have a preference for antenatal counseling but provision of counseling at multiple time-points allows for greater access to, and satisfaction with, counseling.